Anisotropic Ag2S–Au Triangular Nanoprisms with Desired Configuration for Plasmonic Photocatalytic Hydrogen Generation in Visible/Near‐Infrared Region. (19th January 2018) - Lou, Zaizhu; Kim, Sooyeon; Fujitsuka, Mamoru; Yang, Xianguang; Li, Baojun; Majima, Tetsuro
Abstract: Anisotropic Ag2 S‐edged Au‐triangular nanoprisms (TNPs) are constructed by controlling preferential overgrowth of Ag2 S as plasmonic photocatalysts for hydrogen generation. Under visible and near‐infrared light irradiation, Ag2 S‐edged Au‐TNPs exhibit almost fourfold higher efficiency (796 µmol h −1 g −1 ) than those of Ag2 S‐covered Au‐TNPs (216 µmol h −1 g −1 ) and pure Au‐TNPs in hydrogen generation. A single‐particle photoluminescence study demonstrates that the plasmon‐induced hot electrons transfer from Au‐TNPs to Ag2 S for hydrogen generation. Finite‐difference‐time‐domain simulations verify that the corners/edges of Au‐TNPs are high‐curvature sites with maximum electric field distributions facilitating hot electron generation and transfer. Therefore, Ag2 S‐edged Au‐TNPs are efficient plasmonic photocatalyst with the desired configurations for charge separation boosting hydrogen generation. Abstract : Anisotropic Ag2 S‐edged Au‐triangular nanoprisms (TNPs), exhibiting almost four‐fold higher efficiency than Ag2 S‐covered ones in hydrogen generation under visible‐NIR light irradiation, are synthesized by controlling preferential overgrowth of Ag2 S. Single‐particle photoluminescence and finite‐difference‐time‐domain studies demonstrate that Ag2 S‐edged Au‐TNPs have the desired configuration for plasmon‐induced hot electron transfer and charge separation, leading to highly efficient hydrogen generation.